Curricular Clouds of (Un)Knowing: Learning About Mystery From the Mystic Traditions - Tsun Haggarty, Holly (Journal of the Canadian Association for Curriculum Studies, 2025)
Curricula have traditionally been concerned with proposing intentions and expectations for the teaching and learning of knowledge. What if curriculum conversed not only with the known, but the unknowable—with mystery? In this work, I investigate mystic traditions to learn about mystery. I come to a characterization of mystery as the dialectical condition of knowing while at the same time not knowing. Mystery is also an epithet of ultimate reality—a wholeness, which, all the while not completely knowable, nonetheless, attracts the utmost attention in its possibility for wisdom and meaningful transformation. The mystic traditions remind that mystery is an ineluctable feature of any metaphysical theory that aims to explicate ultimate reality, and because of this, belief is an inherent aspect of any metaphysical understanding. Furthermore, because metaphysical belief underpins our understanding of knowledge, a curriculum that invites mystery invites exploring, discerning and acting on existential beliefs. The mystic traditions proffer a way to approach mystery, namely the contemplative pathway, which can be engaged as both epistemological model and method. Mystic traditions also demonstrate how to deal with paradox, one of which is engaging reason to prepare for revelation. Thus, I conclude my essay with a poetic inquiry.